Ecological Education In Laudato Si' - Joshtrom Isaac Kureethadam (The Francis de Sales Scientific Society (TNFS.PL), 2022)
Laudato Si', Pope Francis' recent encyclical on care for our common home, reminds us that ecological education is vital to becoming more responsible stewards of our home planet. In the face of the contemporary ecological crisis, we stand in need of a deep personal transformation and a radical renewal of our life-styles. Here the role of education is paramount. Pope Francis calls for an ecological education capable of establishing a new covenant between humanity and the natural world. According to the Pope, we need a holistic education that can re-establish harmony with nature, our fellow human beings and the Transcendent. The Pope also speaks of the variety of settings for education to ecological citizenship: schools, families, media, catechesis, houses of religious formation, etc. Education towards ecological citizenship is the need of the hour in this crucial moment of planetary emergency.